Vinterupplevelser på naturis : En utvecklingsstrategi för Piteå som skridskodestination utifrån ett upplevelseperspektiv - Forsberg, Ida; Sandström, Charlotta (2011)
The purpose of this essay was to formulate a strategic development plan for Piteå with the aim of becoming a successful ice-skating destination. The question at issue is therefore, how can Piteå become a successful ice-skating destination? We used a qualitative method and to gather material we executed five interviews and processed relevant literature on destination development. We used an abductive approach which favors a work process where we start with reality and then work our way to the theoretical realm, we then returned to reality and then advance to the theoretical realm once more, this works by verifying formulated theories by testing them in reality. We analyzed the results with a pre-understanding of experience production and economy and concluded that a strategic development plan for Piteå as an ice-skating destination should contain ways to;• Work with destination development on a municipal level• Execute and apply a risk analysis and a contingency plan• Maintain an economic, social and environmental sustainable destination• Create an image for Piteå as a winter destination• Offer events of a certain experience qualityWe reached the conclusion that Piteå have great possibilities to become a successful ice-skating destination, in order to achieve this, there has to be collaboration between the population, the municipality and the local businesses towards a common goal. Validerat; 20110703 (anonymous)